Bronchial hyperresponsiveness and the development of asthma and COPD in asymptomatic individuals: SAPALDIA Cohort Study. Issue 8 (2nd May 2006) - Brutsche, M H; Downs, S H; Schindler, C; Gerbase, M W; Schwartz, J; Frey, M; Russi, E W; Ackermann-Liebrich, U; Leuenberger, P
Abstract : Background: Bronchial hyperresponsiveness (BHR) is a common feature of asthma. However, BHR is also present in asymptomatic individuals and its clinical and prognostic significance is unclear. We hypothesised that BHR might play a role in the development of chronic obstructive pulmonary disease (COPD) as well as asthma. Methods: In 1991 respiratory symptoms and BHR to methacholine were evaluated in 7126 of the 9651 participants in the SAPALDIA cohort study. Eleven years later 5825 of these participants were re-evaluated, of whom 4852 performed spirometric tests. COPD was defined as an FEV1 /FVC ratio of <0.70. Results: In 1991 17% of participants had BHR, of whom 51% were asymptomatic. Eleven years later the prevalence of asthma, wheeze, and shortness of breath in formerly asymptomatic subjects with or without BHR was, respectively, 5.7% v 2.0%, 8.3% v 3.4%, and 19.1% v 11.9% (all p<0.001). Similar differences were observed for chronic cough (5.9% v 2.3%; p = 0.002) and COPD (37.9% v 14.3%; p<0.001). BHR conferred an adjusted odds ratio (OR) of 2.9 (95% CI 1.8 to 4.5) for wheezing at follow up among asymptomatic participants. The adjusted OR for COPD was 4.5 (95% CI 3.3 to 6.0). Silent BHR was associated with a significantly accelerated decline in FEV1 by 12 (5–18), 11 (5–16), and 4 (2–8) ml/year in current smokers, former smokers and never smokers, respectively, at SAPALDIA 2. Conclusions: BHR is a risk factor for an accelerated decline in FEV1 and the development of asthma and COPD, irrespective of atopic status. Current smokers with BHR have a particularly high loss of FEV1 .